2017
DOI: 10.1007/s10461-017-1962-8
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of a Tenofovir Disoproxil Fumarate Vaginal Ring for HIV Prevention Among Women in New York City

Abstract: Vaginal rings for pre-exposure prophylaxis are a female-initiated HIV prevention method that does not require daily or coitally-dependent dosing. As part of a randomized placebo-controlled trial of a tenofovir disoproxil fumarate intravaginal ring, we assessed product acceptability through in-depth interviews with 18 women during and after 14 days of continuous use. Women reported that the ring was comfortable with few side effects, regardless of experimental arm. However, interest in future use by this cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…In particular, some women did not feel that PrEP was necessary unless their current relationship ended and they began dating other people. This finding is consistent with two qualitative studies that found women stopped using PrEP because their perceived season of risk ended (Namey et al, 2016;Watnick, Keller, Stein, & Bauman, 2018). Season of risk recognizes that a person may only use PrEP during perceived times of increased risk of HIV infection such as during the dating period, the beginning of a relationship, and when trying to conceive (Namey et al, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…In particular, some women did not feel that PrEP was necessary unless their current relationship ended and they began dating other people. This finding is consistent with two qualitative studies that found women stopped using PrEP because their perceived season of risk ended (Namey et al, 2016;Watnick, Keller, Stein, & Bauman, 2018). Season of risk recognizes that a person may only use PrEP during perceived times of increased risk of HIV infection such as during the dating period, the beginning of a relationship, and when trying to conceive (Namey et al, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…However, the extent of vaginal ring staining is highly variable among women. Since women can easily remove and inspect rings, any observed discolouration may be a concern for some users ( van der Straten et al, 2016 ; Duby et al, 2020 ; Watnick et al, 2018 ; Stifani et al, 2018 ). Patient education may help to reduce the levels of concern or non-adherence associated with discolouration.…”
Section: Resultsmentioning
confidence: 99%
“…Acceptability studies have demonstrated that vaginal rings releasing steroid hormones or antiretrovirals are generally well-accepted, particularly after women have gained experience using the products ( Montgomery et al, 2017 ; RamaRao et al, 2018 ; van der Straten et al, 2012 ; Novák et al, 2003 ; Kestelyn et al, 2018 ; Nel et al, 2016b ). However, some women have voiced concerns regarding vaginal ring hygiene, particularly during menses ( van der Straten et al, 2016 ; Duby et al, 2020 ; Watnick et al, 2018 ). Surface discolouration of silicone elastomer vaginal rings during clinical use has been reported in the scientific literature ( Kiser et al, 2012 ; van der Straten et al, 2016 ; Kestelyn et al, 2018 ; Ballagh, 2001 ; Murphy et al, 2019a ; Das et al, 2015 ; Murphy et al, 2019b ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure of rings to other household or personal hygiene products could potentially affect their in vivo performance. In studies examining acceptability of a tenofovir disoproxil fumarate ring among women from New York, users were concerned about the ring potentially absorbing blood and getting dirty if it remained inserted during menses (Watnick et al, 2018). In a previous study, between 4 and 18% of women reported removing the ring either during menses or for periodic cleaning (Montgomery et al, 2012).…”
Section: Introductionmentioning
confidence: 99%